2016
DOI: 10.1371/journal.pone.0156400
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Capture of Drug Resistant-Influenza Virus by Live Imaging of Sialidase Activity

Abstract: Influenza A and B viruses possess a neuraminidase protein that shows sialidase activity. Influenza virus-specific neuraminidase inhibitors (NAIs) are commonly used for clinical treatment of influenza. However, some influenza A and B viruses that are resistant to NAIs have emerged in nature. NAI-resistant viruses have been monitored in public hygiene surveys and the mechanism underlying the resistance has been studied. Here, we describe a new assay for selective detection and isolation of an NAI-resistant virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In order to examine the optimal concentration of calcium ion and the optimal temperature for BTP3-Neu5Ac reaction, we incubated IAV or IBV with 100 μM BTP3-Neu5Ac under varying conditions of CaCl 2 concentration and temperature. Sialidase activity was compared with that in the original experimental condition, 37°C incubation for 10 min in the presence of 1.0 mM CaCl 2 , as described in our previous reports [ 36 , 41 ]. Viral sialidase activity was increased up to 1.3 fold at 50 mM CaCl 2 ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to examine the optimal concentration of calcium ion and the optimal temperature for BTP3-Neu5Ac reaction, we incubated IAV or IBV with 100 μM BTP3-Neu5Ac under varying conditions of CaCl 2 concentration and temperature. Sialidase activity was compared with that in the original experimental condition, 37°C incubation for 10 min in the presence of 1.0 mM CaCl 2 , as described in our previous reports [ 36 , 41 ]. Viral sialidase activity was increased up to 1.3 fold at 50 mM CaCl 2 ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Drug-resistant viruses can retain sialidase activity even with the amount of an NAI that inhibits sialidase activity of drug-sensitive viruses. We have reported selective detection and selective isolation of drug-resistant viruses at the levels of virus culture and infected cells by BTP3-Neu5Ac reaction in the presence of NAIs [ 41 ]. It is expected that the BTP3-based filter method will also be able to detect such resistant viruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we showed that drug-resistant viruses can be directly isolated from the virus-infected cell population (focus) stained with BTP3-Neu5Ac in the presence of NA inhibitors. 23) …”
Section: )mentioning
confidence: 99%
“…MDCK cells on a 6-well plate were inoculated with mixtures of oseltamivir-resistant 738 and oseltamivir-sensitive 838 at various ratios (%) as described previously. 23) MDCK cells were visualized with 2 mM BTP3-Neu5Ac dropped onto the overlaid agarose-containing SFM with or without 1000 nM oseltamivir after incubation at 37°C for 2 d. Fluorescent images of the plate were observed under UV irradiation at 365 nm.…”
Section: Fluorescence Imaging Of Paramyxo-virus-infected Cellsmentioning
confidence: 99%